2019
DOI: 10.1155/2019/2137538
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SNPs/Haplotypes of IL10 and IFNG on the Development of Diffuse Large B-Cell Lymphoma

Abstract: The purpose of this study was to assess the influence of single-nucleotide polymorphisms (SNPs) on cytokine genes in the development of diffuse large B-cell lymphoma (DLBCL). One hundred and twelve patients and 221 controls were investigated. Among them, 97 patients treated with R-CHOP were subdivided into two groups: (i) complete remission of the disease and (ii) patients who progressed to death, relapsed, or had disease progression. The SNPs investigated by PCR-SSP were TNF -308G>A (rs1800629), IFNG +874A>T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…18 In addition, the rs1800795 SNP was already associated with T2DM, 73,74 besides obesity 75 and lots of types of cancer. 76,77 Here, our analysis of the rs1800795 SNP (IL6 gene) showed no significant results for the susceptibility to periodontitis, but when focusing the association of both T2DM and periodontitis, we found that the men with CC genotype were 88% less prone to develop P + T2DM, with a true effect on the population between 98% and 30% (adjusted OR = 0.12, 95% CI = 0.02-0.70, P = .01).…”
Section: Discussionmentioning
confidence: 59%
“…18 In addition, the rs1800795 SNP was already associated with T2DM, 73,74 besides obesity 75 and lots of types of cancer. 76,77 Here, our analysis of the rs1800795 SNP (IL6 gene) showed no significant results for the susceptibility to periodontitis, but when focusing the association of both T2DM and periodontitis, we found that the men with CC genotype were 88% less prone to develop P + T2DM, with a true effect on the population between 98% and 30% (adjusted OR = 0.12, 95% CI = 0.02-0.70, P = .01).…”
Section: Discussionmentioning
confidence: 59%
“…The ACC haplotype is associated with moderate IL-10 production [35] , but its role in different diseases is controversial. Marangon et al [36] showed that this haplotype was a protective factor in diffuse large B-cell lymphoma, while Gao et al [28] showed that it was associated with an increased risk of IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…ACC haplotype is associated with moderate IL-10 production, 47 but its role in different diseases is controversial. Marangon et al 48 showed that this haplotype was a protective factor in case of diffuse large B-cell lymphoma, while Gao et al 39 showed that it was associated with an increased risk of IgA nephropathy.…”
Section: F I G U R Ementioning
confidence: 99%